ответ: 288; 333; 558; 9468; 576; 891; 7839; 765; 936
Пошаговое объяснение:
число делится на 9, если сумма его цифр делится на 9
288 (2+8+8=18; 18 : 9 = 2 ) - делится на 9
333 ( 3 + 3 + 3 = 9; 9 : 9 = 1 ) - делится на 9
444 ( 4 + 4 + 4 = 12; 12 не делится на цело на 9) - не делится
558 ( 5 + 5 + 8 = 18; 18 : 9 = 2 ) - делится на 9
9468 ( 9 + 4 + 6 + 8 ) = 27; 27 : 9 = 3 ) - делится на 9
507 ( 5 + 0 + 7 = 12; 12 : 9 не делится на цело на 9 ) - не делится
8645 ( 8 + 6 + 4 + 5 = 23; 23 : 9 - не делится на цело ) - не делится
576 ( 5 + 7 + 6 = 18; 18 : 9 = 2 ) - делится на 9
802 ( 8 + 0 + 2 = 10; 10 : 9 - не делится на цело) - не делится
891 ( 8 + 9 + 1 = 18; 18: 9 = 2 ) - делится на 9
7839 ( 7 + 8 + 3 + 9 = 27 ; 27 : 9 = 3 ) - делится на 9
765 (7 + 6 + 5 ) = 18; 18 : 9 = 2 ) -делится на 9
781 ( 7 + 8 + 1 =16 ; 16 : 9 - не делится на цело) - не делится на 9
936 (9 + 3 + 6 = 18 ; 18 : 9 = 2 ) - делится на 9
288 : 9 = 32
333 : 9 = 37
558 : 9 = 62
9468 : 9 = 1052
576 : 9 = 64
891 : 9 = 99
7839 : 9 = 871
765 : 9 = 85
936 : 9 = 104
число делится на 9, если сумма его цифр делится на 9
288 (2+8+8=18; 18 : 9 = 2 ) - делится на 9
333 ( 3 + 3 + 3 = 9; 9 : 9 = 1 ) - делится на 9
444 ( 4 + 4 + 4 = 12; 12 не делится на цело на 9) - не делится
558 ( 5 + 5 + 8 = 18; 18 : 9 = 2 ) - делится на 9
9468 ( 9 + 4 + 6 + 8 ) = 27; 27 : 9 = 3 ) - делится на 9
507 ( 5 + 0 + 7 = 12; 12 : 9 не делится на цело на 9 ) - не делится
8645 ( 8 + 6 + 4 + 5 = 23; 23 : 9 - не делится на цело ) - не делится
576 ( 5 + 7 + 6 = 18; 18 : 9 = 2 ) - делится на 9
802 ( 8 + 0 + 2 = 10; 10 : 9 - не делится на цело) - не делится
891 ( 8 + 9 + 1 = 18; 18: 9 = 2 ) - делится на 9
7839 ( 7 + 8 + 3 + 9 = 27 ; 27 : 9 = 3 ) - делится на 9
765 (7 + 6 + 5 ) = 18; 18 : 9 = 2 ) -делится на 9
781 ( 7 + 8 + 1 =16 ; 16 : 9 - не делится на цело) - не делится на 9
936 (9 + 3 + 6 = 18 ; 18 : 9 = 2 ) - делится на 9
288 : 9 = 32
333 : 9 = 37
558 : 9 = 62
9468 : 9 = 1052
576 : 9 = 64
891 : 9 = 99
7839 : 9 = 871
765 : 9 = 85
936 : 9 = 104
ответ: 288; 333; 558; 9468; 576; 891; 7839; 765; 936
2)а) F(x)=4x^4/4+sinx+С=x^4+sinx+С
б) F(x)=4х/x^6/6-3х+С=24х/x^6-3х+С=24/x^5-3х+С
3)а) f(x)=x^2+8х+16 F(x)=x^3/3+8x^2/2+16х+С F(-4)=(-4)^3/3+4*(-4)^2+16*(-4)+С
-64/3+64-64+С=3 С=3+64/3=24 1/3
F(x)=x^3/3+4x^2+16х+24 1/3
б) F(x)=х/x^(3/2)/3/2+С=3/2х/x^(3/2)+С
F(4)=3/2*4/x^(3/2)+С=4
6/8+С=4
С=4-3/4=3 1/4
F(x)=3/2х/x^(3/2)+3 1/4